Dancing in Circles. Baudrillard and Death - D’Andrea, Fabio (Italian Sociological Review, 2017)
With the aid of a Baudrillardian text that sociology mostly overlooked, this essay aims at highlighting the author’s closeness to the mythanalytic core of French socio-anthropology, particularly Durand and Maffesoli – thinkers to whom Baudrillard has been connected by strong friendly, even more than intellectual, ties. In Symbolic Exchange and Death (1984 [1976]), he puts forward a heterodox view of the social, when Modernity is still at its apex. He does so in no uncertain terms: ‘symbol’ and ‘death’ in the title mark a radical moving away from the prevailing ideology; more so the conjugation of serious things like economy and goods with fuzzy entities such as symbols, vestiges of a cultural infancy now left behind. Today this is not, however, the most appealing aspect of this book: the Modern attempt at rebuilding reality starting from the market has failed, but this is only one of the aspects of the paradigmatic collapse that is crushing the XXI century. Much more is at stake and most of it is here suggested: reversibility, cycle, death. The play of simulacra and the dissolution of reality are already clearly formulated, even though more can be said about the transfiguration of objects, but it is also possible to take Baudrillard’s ideas beyond their intended range by focusing on a moment in his career when his path could have gone in other directions than those it actually took. It could have led him to less modern developments: the symbolic and corporeal space that is hinted at here is the Elsewhere of Modernity that in subsequent works unfortunately disappears.